Study on the Impact of Information, Interface, and Interactivity of Digital Marketing Channels on the Intention to Visit Thanh Hoa Tourist Destinations: The Mediating Role of Tourist Satisfaction on Digital Marketing Application - Xuan, Nguyen Thi Thanh; Nuong, Le Thi (European Journal of Science, Innovation and Technology, 2024)
The study examines the impact of information, interface, and interactivity of digital marketing channels on tourist satisfaction with the current status of digital marketing applications in Thanh Hoa. In addition, the impact of tourist satisfaction on the intention to visit Thanh Hoa’s tourist destination is also tested in the research model. This study uses a convenient random data collection method for 305 people across the country who have searched for tourist information about Thanh Hoa on digital marketing channels; data collected from the survey were cleaned and analyzed using Smart PLS4 software. The results of this study have demonstrated that information, interactivity, and interface of digital marketing channels not only directly affect satisfaction but also indirectly affect the intention to visit through satisfaction. The study provides some theoretical and practical implications that the study can achieve.